Fiber-Reinforced composite resin bridges as a treatment alternative for posterior missing tooth - Waskitho, Arief; Putri, Anggun Kharisma (Faculty of Dentistry, Universitas Gadjah Mada, 2024)
Dental restoration alternatives for posterior missing tooth range from dental bridges to implant dentures. Fiber-reinforced composite (FRC) resin bridge is one option for the replacement of a single tooth missing. FRC bridge is known as an alternative replacement method for single posterior missing tooth with minimally invasive preparation of abutment teeth. The simplicity of the production method in the FRC bridge provides the possibility of a single-visit bridge treatment. This report aims to present two successful treatments for missing posterior tooth by two different methods of immediate restoration using the FRC resin bridge. Treatments were performed directly using two different fiber materials, pre-impregnated quartz unidirectional fiber, and quartz fiber post. The use of unidirectional quartz fiber and quartz fiber post in the posterior tooth exhibited superior results due to its strength and geometry of fiber placement. In conclusion, the fiber-reinforced composite bridge is a possible option for managing the upper posterior missing tooth.